Building a Spatial Database by Developing a Work Environment to Accomplish the Automatic Transfer Process for Remote Sensing Data from Raster to Linear - Diaa Al-Berhawi (Al-Rafidain Journal of Computer Sciences and Mathematics)
In this paper a develop an working environment for building spatial database by utilizing ArcView Geographic Information System software package and IDRISI software package for remotely sensed images processing is obtained. Through working environment remotely sensed images representation transformed from raster form to vector form. Programming environment of the ArcView and IDRISI software packages utilized to achieve spatial database building from remotely sensed images automatically. The results of the proposed working environment show efficiency in building spatial database in accurate and quick manner. Thus, these spatial database can be used in Geographic Information System applications.